(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Purpose: To suggest that electron beams with almost the same amount of energy could be used instead of traditional accelerators for high-energy electron radiation therapy. Methods: Electron beams with energy up to hundred MeV, 1.8% energy spread, 125 pC charges and a few mDivergences have been made with a clustered gas plasma that is 3 mm long and It operates on a laser pulse with a peak power of up to 100 TW. High-quality electron beams and dependable laser propagation are produced by optimizing experimental factors including laser contrast and the time of the laser-plasma interaction. Results: In addition to the self-focusing effect, clustered gas has two other crucial properties: a strong local electron density and effective ultra-short laser pulse absorption. Therefore, high electron densities and ionization levels might produce intense electron beams with a high charge. Our test has shown that the gas jet clusters affect the Wakefield evolution and laser propagation, resulting in steady laser guiding and high-quality electron beams. Conclusion: These findings demonstrate that a beam clustered gas target offers a novel method of injecting electrons and has a lot of potential for making collimated electron beams with a high beam charge from a single source of energy. For medical applications like radiation therapy, you need stable, repeatable, and strong enough single-energy electron beams Laser-sped electron beams could be a good way to do radiation therapy in the future. But there are some technical problems that need to be solved before they can be used in real life.